A Case Report on Neurocysticercosis in Children - Priya, Palla Kranthi; Sri, Vedurupaka Sushma; Abhishek, Murre; Singh, Nisha; Kumar, Amit; Chakravarthy, G Kalyana (Indian Journal of Pharmacy Practice)
Neurocysticercosis is a parasitic disease which is caused by the incidental ingestion of Taenia solium eggs (pork tapeworm) through the contaminated food. Neurocysticercosis shows its effect on the nervous system and it has been the main cause of acquired epileptic episodes and it was majorly seen in developing countries, and it is more prevalent in some parts of subcontinents like Asia and Sub-Saharan Africa. It was reported that large group of US immigrants are known to suffer from this disease. The major factor which can cause neurocysticercosis is poor sanitation and unhygienic food. The patients may have symptoms of epilepsy, headache, memory problems and thinking problems. Cysterici undergoes different changes in the brain, subarachnoid space and spinal cord leads to Neurocysticercosis. Neurocysticercosis is preventable, and probably eradicable. Eventually, the cysts either resolve or form a calcified granuloma, which is associated with seizures if it is located in the brain. It is estimated that 30% cases will experience epilepsy.
Keywords: Neurocysticercosis; Epilepsy; Immune attack